2011
DOI: 10.1016/j.atmosenv.2010.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of antioxidants on hydroxyl radical production from individual and mixed transition metals in a surrogate lung fluid

Abstract: Inhalation of ambient particulate matter causes morbidity and mortality in humans. One hypothesized mechanism of toxicity is the particle-induced formation of reactive oxygen species (ROS) – including the highly damaging hydroxyl radical (·OH) – followed by inflammation and a variety of diseases. While past studies have found correlations between ROS formation and a variety of metals, there are no quantitative measurements of ·OH formation from transition metals at concentrations relevant to 24-hour ambient pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(154 citation statements)
references
References 44 publications
12
141
1
Order By: Relevance
“…Previous studies have shown that redox-active components such as transition metals and quinones can induce ROS formation in surrogate lung lining fluid upon interactions with antioxidants (Charrier and Anastasio, 2011;Charrier et al, 2014). This study also implies that ROS can be formed in lung lining fluid upon inhalation and respiratory deposition of atmospheric aerosol particles.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that redox-active components such as transition metals and quinones can induce ROS formation in surrogate lung lining fluid upon interactions with antioxidants (Charrier and Anastasio, 2011;Charrier et al, 2014). This study also implies that ROS can be formed in lung lining fluid upon inhalation and respiratory deposition of atmospheric aerosol particles.…”
Section: Discussionmentioning
confidence: 62%
“…Fe is often linked to the oxidative damage caused by particles (Valavanidis et al, 2000;Han et al, 2001;See et al, 2007;Di Pietro et al, 2009;Charrier and Anastasio, 2011), and soluble Fe affects oxidative capacity through (Shi et al, 2003;Risom et al, 2005;Vidrio et al, 2008;Nawrot et al, 2009). The ICP-MS analysis indicated that, although total Fe concentration in the Lanzhou PM 10 samples was much higher than that in the soluble fraction, the concentration of soluble Fe was significant, reaching as much as 1105 μg/g.…”
Section: Correlation Between Heavy Metal Concentration and Bioreactivitymentioning
confidence: 98%
“…However, in very small (ultrafine) size ranges, these particles have been linked with significant oxidative stress mediated toxicity (Duffin, Mills & Donaldson, 2007). Some metals, such as zinc oxide, will dissolve in the body (Gilmour et al, 2006;Charrier & Anastasio, 2011). Zinc ions have many physiological functions, but they can also interfere with the body's homeostasis, leading to such adverse effects as oxidative stress and inflammation.…”
Section: Clinical Studies and Toxicological Studiesmentioning
confidence: 99%